ANALISIS USABILITY APLIKASI BRIMO DENGAN MENGGUNAKAN METODE KUESIONER DAN MODEL DELONE & MCLEAN - Nur Muhammad Asnadi; Eva Khudzaeva (JURNAL PERANGKAT LUNAK, 2023)
The usage of internet and mobile banking in Indonesia has experienced significant growth and provided positive impacts for users. One popular mobile banking application is BRImo from Bank BRI. The increase in application usage is driven by the COVID-19 pandemic and the extensive development of digital banking services. The objective of this research is to evaluate customer satisfaction levels with the BRImo application and analyze the usability factors that influence satisfaction. The NAU (Nielsen Attributes of Usability) questionnaire method and the DeLone and McLean model are employed to achieve these objectives. A g-form questionnaire consisting of 20 statement items is distributed to collect data. Additionally, 7 hypotheses are formulated to test the relationships among the factors influencing customer satisfaction. After the calculation, the researcher found that the BRImo application has a usability level of 76.57%. This result indicates that the application has a fairly good level of usability. In addition, based on the analysis, all hypotheses in this study were accepted, marked by a very strong correlation between the variables. This indicates that the factors investigated have a significant impact on the usability level of the application.